Improving knowledge sharing through intrinsic motivation in the integration of self determination theory and theory of reason for action - Anis Okta Cahyaningrum (Institute of Computer Science (IOCS), 2023)
One source of an organization's competitive advantage is knowledge. Knowledge plays an important role in innovation and performance in organizations in previous studies. The purpose of this study is to investigate the influence of motivation in information sharing. This research is motivated by intrinsic factors (the joy of helping others). The Self Determination Theoty and Theory of Reason Action describe the mechanism. In order to describe the method by which motivation influences information sharing, knowledge sharing intents are utilized. The findings of testing the hypothesis indicate that intrinsic desire positively influences information sharing behavior and that knowledge sharing intentions are fully regulated.